Integration of altimetric lake levels and GRACE gravimetry over Africa: Inferences for terrestrial water storage change 2003–2011. Issue 12 (31st December 2014) - Moore, P.; Williams, S. D. P.
Abstract: Terrestrial water storage (TWS) change for 2003– 2011 is estimated over Africa from GRACE gravimetric data. The signatures from change in water of the major lakes are removed by utilizing kernel functions with lake heights recovered from retracked ENVISAT satellite altimetry. In addition, the contribution of gravimetric change due to soil moisture and biomass is removed from the total GRACE signal by utiliz ing the GLDAS land surface model. The residual TWS time series, namely groundwater and the surface waters in rivers, wetlands, and small lakes, are investigated for trends and the seasonal cycle using linear regression. Typically, such analyses assume that the data are temporally uncorrelated but this has been shown to lead to erroneous inferences in related studies concerning the linear rate and acceleration. In this study, we utilize autocorrelation and investigate the appropriate stochastic model. The results show the proper distribution of TWS change and identify the spatial distribution of significant rates and accelerations. The effect of surface water in the major lakes is shown to contribute significantly to the trend and seasonal variation in TWS in the lake basin. Lake Volta, a managed reservoir in Ghana, is seen to have a contribution to the linear trend that is a factor of three greater than that of Lake Victoria despite having a surface area one‐ eighth of that of Lake Victoria. Analysis also shows the confidence levels of the deterministic trend and acceleration identifying areas where the signatures are most likely due to a physical deterministic cause and not simply stochastic variations. Key Points: Terrestrial water change (2003–2010) for Africa from GRACE gravimetric data Gravimetric signatures from change in surface water in lakes Autocorrelation and appropriate stochastic model